How Can Patient’s Risk Dictate the Timing of Endoscopy in Upper Gastrointestinal Bleeding? - Freitas,Marta (2022)
Abstract Introduction: Although upper gastrointestinal bleeding (UGIB) management has improved substantially in the last decades, there is still much controversy regarding the optimal timing for performance of endoscopy. Recent guidelines suggest performing an early endoscopy within 24 h of nonvariceal UGIB (NVUGIB) presentation, although its impact on patients with different bleeding risks remains unclear. Aim: To evaluate the impact of performing endoscopy within 24 h on NVUGIB outcomes and to compare it in patients with lower-risk vs. higher-risk bleeding. Methods: This is a retrospective cohort study including consecutive patients undergoing upper endoscopy for suspected NVUGIB over 4 years. Demographic, clinical, biochemical, endoscopic, and outcome data were collected. Lower-risk bleeding was defined as a Glasgow-Blatchford score (GBS) <12 and higher-risk bleeding was defined as a GBS ≥12. Results: A total of 298 patients with suspected NVUGIB were included, 55% of whom had higher-risk bleeding. Endoscopy was performed within 24 h in 62.1% of the patients. In lower-risk bleeding patients, performance of endoscopy within 24 h was associated with a higher need for endoscopic treatment (OR = 2.6; 95% CI 1.2-5.7; p = 0.004), a lower 30-day mortality (OR = 0.41; 95% CI 0.27-0.63; p = 0.03), and a lower need for transfusion (OR = 0.58; 95% CI 0.36-0.92; p = 0.02). In higher-risk bleeding patients, there were no statistically significant differences in NVUGIB outcomes in performing endoscopy within 24 h. Conclusion: Endoscopy within 24 h of presentation was associated with a lower need for transfusion, a higher need for endoscopic treatment, and a lower 30-day mortality in lower-risk NVUGIB patients. Thus, performing endoscopy within the first 24 h of presentation can have a positive impact on NVUGIB outcomes even in lower-risk bleeding.